2021
DOI: 10.47626/2237-6089-2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of the Resilience Scale for Brazilian caregivers of people with Alzheimer’s disease

Abstract: Introduction:Resilience is a dynamic process that acts to modify the effects of an adverse life event. In this study, we aimed to test the construct validity of the Resilience Scale by employing exploratory and confirmatory procedures, and to investigate the relationship between caregiver's resilience and clinical status of people with Alzheimer's disease. Methods: A sample of 143 dyads of people with Alzheimer's disease and their primary caregivers were included. Results: The total Resilience Scale mean score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The relationship among this triad, resilience, grit and perseverance, is, however, evident in the large body of literature [58][59][60] . Like resilience, grit is believed to have more attributes related to constructs such as self-efficacy, conscientiousness, perseverance, mindset, self-control, mindfulness 31,32 and equanimity [32][33][34] . This notion is in good agreement with our theoretical model of resilience that should constitute resilience in addition to perseverance, that is, wisdom, patience (or tolerance), loving-kindness, perseverance, mindfulness and equanimity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship among this triad, resilience, grit and perseverance, is, however, evident in the large body of literature [58][59][60] . Like resilience, grit is believed to have more attributes related to constructs such as self-efficacy, conscientiousness, perseverance, mindset, self-control, mindfulness 31,32 and equanimity [32][33][34] . This notion is in good agreement with our theoretical model of resilience that should constitute resilience in addition to perseverance, that is, wisdom, patience (or tolerance), loving-kindness, perseverance, mindfulness and equanimity.…”
Section: Discussionmentioning
confidence: 99%
“…79% ( n = 158) were female; 82% ( n = 163) were married; 62% ( n = 122) caring for spouse; 23% ( n = 65) caring for parent; 5.1% ( n = 10) caring for ‘other’ Type of dementia: Alzheimer’s Disease or dementia British Columbia, Canada (English) Controlled mixed methods intervention study (Not reported) None specified Ideal internal consistency (time 1 and time 2 α = 0.91) Not hypothesis driven: Responsiveness: There was a significant improvement in resilience from T1 to T2 for the grief coaching intervention group compared to the control group ( F = 10.70, df = 185, p = .009), and there was no change in the control group. Effect sizes not reported Monteiro et al [ 32 ] (To test the construct validity of the Resilience Scale through exploratory and confirmatory procedures, and to investigate the relationship between caregiver’s resilience and clinical status of people with Alzheimer’s disease) N = 143 carers of people with AD; mean age = 58.8 (SD = 14.3); N = 118 females. No other demographic information is presented Rio de Jeneiro, Brazil (Portuguese) Cross-sectional design (Face to face interviews) None specified Adequate to ideal internal consistency α = 0.77 The factor analysis found a four-factor solution—sense of life and self-sufficiency, perseverance, self-confidence and equanimity, and meaningfulness.…”
Section: Resultsmentioning
confidence: 99%